The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0164286
|View full text |Cite
|
Sign up to set email alerts
|

Civility vs. Incivility in Online Social Interactions: An Evolutionary Approach

Abstract: Evidence is growing that forms of incivility–e.g. aggressive and disrespectful behaviors, harassment, hate speech and outrageous claims–are spreading in the population of social networking sites’ (SNS) users. Online social networks such as Facebook allow users to regularly interact with known and unknown others, who can behave either politely or rudely. This leads individuals not only to learn and adopt successful strategies for using the site, but also to condition their own behavior on that of others. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Sabatini and Sarracino () found that the use of SNS is significantly and negatively correlated with trust in unknown others and in public institutions in Italy for the period 2010‐11. Antoci et al () explained the possibly detrimental effects of the use of SNS as a consequence of online incivility, a widespread phenomenon including aggressive and disrespectful behaviors, vile comments, harassment, and hate speech that makes online social environments potentially hostile for users (Rainie et al, ; Duggan, ). The relevance of this phenomenon is illustrated by the PRC, which reports that non‐negligible proportions of SNS users do witness bad behavior on those sites.…”
Section: Sns and Social Capitalmentioning
confidence: 99%
“…Sabatini and Sarracino () found that the use of SNS is significantly and negatively correlated with trust in unknown others and in public institutions in Italy for the period 2010‐11. Antoci et al () explained the possibly detrimental effects of the use of SNS as a consequence of online incivility, a widespread phenomenon including aggressive and disrespectful behaviors, vile comments, harassment, and hate speech that makes online social environments potentially hostile for users (Rainie et al, ; Duggan, ). The relevance of this phenomenon is illustrated by the PRC, which reports that non‐negligible proportions of SNS users do witness bad behavior on those sites.…”
Section: Sns and Social Capitalmentioning
confidence: 99%
“…By employing more interpretable features, it becomes more straightforward to describe the social and communicative dynamics which underpin hate speech as it is used in context. This enables researchers to better understand not just which texts may be linked to hate speech, but also how they communicate hate, evolve in communities, and reinforce conflicts [3,33,47,50].…”
Section: Hate Speech On Social Media: From Classification To Charactementioning
confidence: 99%
“…Events and discussions unfolding of the past year highlight the struggles ahead" (2017, p. 2). Interestingly, Antoci, Delfino, Paglieri, Panebianco, and Sabatini (2016) created a model of interaction between three groups: haters (who engage in hate speech and offensive language) H, politers (who engage in polite behaviour) P, and withdrawers N, in the context of social media and face-to-face interactions. They reported that their model "…suggests that politeness can survive in a world with a fair share of haters only if the payoffs of polite people are not heavily affected by haters" (2006, p. 14).…”
Section: A Crisis In Civic Conscience In the United States?mentioning
confidence: 99%